Optical antennas : linear and nonlinear excitation and emission - Wissert, Matthias Dominik (KIT Scientific Publishing, 2011)
The linear and nonlinear resonance behaviour of optical antennas (metallic nanostructures showing resonance behaviour at optical frequencies) made of gold and aluminum using electron-beam lithography is investigated. Specifically, it is of interest how the emission behaviour is changed by the coupling of two antenna arms via a small gap. Experimental techniques applied include dark-field spectroscopy and two-photon luminescence.